Sequencing of the novel HLA‐B*49:24 and HLA‐DRB1*03:64 alleles. Issue 3 (30th January 2013) - Planelles, D.; Balas, A.; Nagore, E.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> HLA‐B*49:24 shows one nucleotide difference regarding B*49:10 at codon 12 (ATG>GTG). DRB1*03:64 differs from DRB1*03:01:01 in one amino acid residue at position 59, E>Q.